Holiday Advertising in the Borderland: The Specificity of Perception in Latgale Region (Latvia) and Pskov Region (Russia) - Kovzele, Oksana (Technium Social Sciences Journal, 2020)
Holiday advertising is a rather topical object of research that nowadays attracts attention of specialists in various branches opening new perspectives of investigating this phenomenon. One of them is the analysis of the specificity of functioning and perception of holiday advertising in various European and world countries including a comparative perspective of the border zone. The present paper reveals the specificity of the perception of holiday advertising by the example of the south-eastern region of Latvia – Latgale (the major object of the research) and Pskov region that is a part of the north-western federal province of Russia (the minor object of the research) on the basis of interviews carried out in 2018 with the participation of 906 residents of this border area. During the survey, respondents had an opportunity to express their opinion on holiday advertising in general as well as note the positive and negative impacts on a common present-day consumer. Processing of the survey data leads to the conclusion that the notion of holiday advertising in Latgale has been generally crystallized as it is rather often used in daily life, including for the selection of gifts for festive occasions, whereas in Pskov region there is no unified opinion on the essence and significance of holiday advertising yet as, in the respondents’ opinion, its potential is not used to a full extent.